Remedial Learning Implementation Through the Peer-Tutor Method in The Entrepreneurship Course - Sudarwati, Ninik; Suharto, Suharto; Iffah, Nur (Universitas Nusantara PGRI Kediri, 2024)
The global issue appears on the students' problem, especially in remedial learning.The purposes of this study are: (1) to describe the activities of lecturers in classroom management and remedial activities, (2) to describe the activities of students in peer-tutor learning method, (3) to describe students' learning mastery after having remedial activity with the peer-tutor method. The type of this research is action research, consisting of planning, action and observation, reflection, and revision. The action was given in three rounds in the classroom (Classroom Action Research). This research was conducted in STKIP PGRI Jombang, Economic Education Study Program. This research was conducted from August to September 2022. The subject of this research is 44 students of STKIP PGRI Jombang. The object of this study is Break-Even Point (BEP) material. Findings show that the average skill of the lecturer in managing the class and remedial activity in 3 rounds of Classroom Action Research is 3.29% which indicates that the lecturer has succeeded in improving students' achievement.